2009
DOI: 10.1105/tpc.109.065565
|View full text |Cite
|
Sign up to set email alerts
|

Misexpression of FATTY ACID ELONGATION1 in theArabidopsisEpidermis Induces Cell Death and Suggests a Critical Role for Phospholipase A2 in This Process

Abstract: Very-long-chain fatty acids (VLCFAs) are important functional components of various lipid classes, including cuticular lipids in the higher plant epidermis and lipid-derived second messengers. Here, we report the characterization of transgenic Arabidopsis thaliana plants that epidermally express FATTY ACID ELONGATION1 (FAE1), the seed-specific b-ketoacyl-CoA synthase (KCS) catalyzing the first rate-limiting step in VLCFA biosynthesis. Misexpression of FAE1 changes the VLCFAs in different classes of lipids but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 87 publications
0
36
0
Order By: Relevance
“…For example, pPLA and iPLA 2 share a sensitivity against BEL inhibitor (also called HELSS), showing again their close catalytic properties. Regulation of cell death is also inhibited by BEL so that the relevant protein was shown to have characteristics of a pPLA [4,43].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pPLA and iPLA 2 share a sensitivity against BEL inhibitor (also called HELSS), showing again their close catalytic properties. Regulation of cell death is also inhibited by BEL so that the relevant protein was shown to have characteristics of a pPLA [4,43].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the level of wax was reduced to about ~80% of that in the wild type, albeit a semiglaucous phenotype was not visually apparent in the FDH:FAE1 plants. 1 Dye exclusion tests revealed that FDH:FAE1 trichomes …”
mentioning
confidence: 99%
“…Although the expression of FAE1 did affect non-trichome cells (e.g., with regard to the hostpathogen interactions), cytochemical staining revealed that plasma membrane permeabilization, the accumulation of reactive oxygen species (ROS), including hydrogen peroxide, callose deposition and DNA damage only occurred in trichome cells, whereas other epidermal and non epidermal cells showed no signs of cell death. 1 The profiling of acyl-CoA and the glycerophospholipid molecular species and fatty acids revealed that the expression of FAE1 in the epidermis leads to the appearance of increasing chain-length fatty acids in various lipid classes in the plant tissues. 1 FAE1 is a β-ketoacyl-CoA synthase (KCS) which catalyzes the first rate-limiting step in the synthesis of very long-chain fatty acids (VLCFAs) that are longer than C20.…”
mentioning
confidence: 99%
See 2 more Smart Citations